2012
DOI: 10.11591/telkomnika.v10i5.1176
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Design of a Five-Phase Permanent Magnet Synchronous Motor for Underwater Vehicles by use of Particle Swarm Optimization

Abstract: Motor sinkron magnet permanen adalah motor efisien yang memiliki aplikasi luas pada industri listrik. Salah satu aplikasi yang menarik dari motor tersebut adalah kendaraan bawah air. Pada kasus ini, perhatian utama adalah pencapaian volume minimum dan torsi tinggi. Optimasi desain dapat meningkatkan kemampuan sehingga mengurangi volume dan meningkatkan kinerja motor. Pada makalah ini, sebuah metode baru untuk desain optimum dari lima fase surface-mount motor sinkron magnet permanen disajikan untuk mencapai ker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…This table also has shown that DC motors/thrusters draw most of power. Various magnet volume and torque usually give different results [17,18]. For Tech_SAS ROV, 12V/1.3A 1100 GPH bilge pump is chosen and modified into water-proofed DC motor as a thruster [19,20].…”
Section: Tether Cable Designmentioning
confidence: 99%
“…This table also has shown that DC motors/thrusters draw most of power. Various magnet volume and torque usually give different results [17,18]. For Tech_SAS ROV, 12V/1.3A 1100 GPH bilge pump is chosen and modified into water-proofed DC motor as a thruster [19,20].…”
Section: Tether Cable Designmentioning
confidence: 99%
“…A DC motor with permanent magnet connected field [21] was used since the application range of this motor includes the electric wheelchair because of its high torque and power density [22][23]. A windshield wiper motor which uses permanent magnet field was applied in the design.…”
Section: Selection Of Motor and Motor Drivermentioning
confidence: 99%
“…This is why such systems are often equipped with an encoder. Nevertheless, some manufacturers (including Danfoss) offer technical solutions that allow you to control this type of motor without using an encoder [4].…”
Section: Introduction / вступmentioning
confidence: 99%